Strategi Komunikasi D’OZ Radio Bali Dalam Membina Hubungan Dengan Pengiklan - Romario, Bryan; Purnawan, Ni Luh Ramaswati; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
Stakeholders is a group, individual, or a community which could influence or to be influenced by the organization’s goals. In order to get their goals, some organization put high priority on the stakeholders, it aimed to protect sustainability of the organization. Had a good stakeholders relation s was the most important thing to to. D’OZ Radio is an profit organization which put the advertiser as the one of their main stakeholders. Maintained the communication strategy is the most important to do for get the organization’s goals. This research aimed to know which strategy that was used by the Oz Radio Bali, in maintained a good stakeholders relation s . This researched used qualitative method which interviewed, observation, and documentary. Base on the result, D’OZ Radio Bali used persuasive strategy and dialogue strategy in maintain their stakeholders relations with the advertiser as the most important stakeholders. Key words : advertiser, communication strategy , stakeholders, stakeholders relations